The Role of IL-37 and IL-38 in Colorectal Cancer - Dang, Jie; He, Zhiyun; Cui, Xiang; Fan, Jingchun; Hambly, David J.; Hambly, Brett D.; Li, Xun; Bao, Shisan (Frontiers in Medicine, 2022)
Colorectal cancer (CRC) is a major killer. Dysregulation of IL-37 and IL 38, both anti-inflammatory cytokines, is observed in auto immune diseases. The precise regulatory mechanisms of IL-37/IL 38 during the development of CRC remains unclear, but chronic intestinal inflammation is involved in the carcinogenesis of CRC. Constitutive production of colonic IL-37 and IL-38 is substantially reduced in CRC, consistent with an inverse correlation with CRC differentiation. Reduced colonic IL-37 and IL-38 is relating to CRC invasion and distant metastasis, suggesting a protective role for IL-38 within the tumour micro environment. IL-38 is reduced in right-sided CRC compared to left-sided CRC, which is in line with multiple risk factors for right-sided CRC, including the embryonic development of the colon, and genetic differences in CRC between these two sides. Finally, colonic IL-37 and tumour associated neutrophils seem to be independent biomarkers of prognostic value, whereas colonic IL-38 seems to be a reliable and independent biomarker in predicting the 5-year survival post-surgery in CRC. However, there is room for improvement in available studies, including the extension of these studies to different regions/countries incorporating different races, evaluation of the role of multi-drug resistance and different subsets of CRC. It would be useful to determine the kinetics of circulating IL-38 and its relationship with drug resistance/targeted therapy. The measurement of colonic IL-38 at the molecular and cellular level is required to explore the contribution of IL-38 pathways during the development of CRC. These approaches could provide insight for the development of personalised medicine.